SOME CHARACTERIZATIONS FOR THE DIMENSION OF ORDERED MULTISETS - Balogun, F.; Singh, D. (FUDMA JOURNAL OF SCIENCES, 2023)
The paper presents a study of dimension as an important combinatorial parameter of ordered multisets defined over partially ordered base sets. The relationship between the dimension of a partially ordered multiset and that of the underlying generic set is investigated and some results are presented.Mathematics Subject Classification (2010): 06A07, 03E04, 06F25, 91B16
Keywords: Partially ordered multiset, multiset linear extension, multiset realizer, dimension